ANALISIS PENGARUH RISIKO KREDIT, INTERMEDIASI PERBANKAN, RISIKO LIKUIDITAS, DAN EFISIENSI MANAJEMEN TERHADAP PROFITABILITAS PERBANKAN INDONESIA (Studi Kasus pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Arindi, Glady Precillia; Mawardi, Wisnu (Diponegoro Journal of Management, 2016)
This study aims to examine the effect of credit risk, banking intermediation, liquidity risk, and management efficiency to banking profitability. The dependent variables in this study are Return On Assets (ROA) and Return On Equity (ROE). Meanwhile, the independent variables in this study are Allowance for Impairment Losses Ratio (CKPN), Loans to Deposits Ratio (LDR), Liquidity Gap, and Operating Expenses to Operating Incomes Ratio (BOPO).Â  The sampling technique is conducted by purposive sampling method. The number of total samples in this study is 9 conventional commercial banks listed on the Indonesia Stock Exchange (IDX) in 2010-2014. Data processing was performed using multiple linear regression analysis through classic assumption test beforehand.Â The results using ROA as the dependent variable showed that CKPN and LDR have a positive and significant effect on ROA, BOPO has a negative and significant effect on ROA, and Liquidity Gap has a positive but insignificant effect on ROA. Meanwhile, the results of this research using ROE as dependent variable showed that LDR and BOPO have a negative and significant effect on ROE, CKPN has a positive but insignificant effect on ROE and Liquidity Gap has a negative but insignificant effect on ROE. The results concluded that the profitability of banks can be influenced by CKPN, LDR, and BOPO.